The relationship between serum uric acid level and concentration of proangiogenic endothelial progenitor cells in chronic heart failure patients - A. A. Kremzer (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Serum uric acid (SUA) is considered as a marker of nature progression of chronic heart failure (CHF) mediated cardiovascular remodeling. Progression of CHF associates with declining of circulating endothelial progenitor cells (EPCs) in the peripheral circulation.